Radiogenic components of the nigerian tar sand deposits (2009)
A combination of factors has prevented the exploitation of the Nigerian tar sand deposits to date, among which is the environmental factor which may pose some dangers to both physical and biological components of the area of occurrence. Gamma ray spectrometric analysis was carried out on samples of bituminous sand deposits in parts of Southwestern Nigeria.The aims were to determine the presence and level of radioactivity of selected radionuclides and to assess the possible impact on the environment, and provide geochemical baseline that could be useful in planning appropriate environmental management programs that will reduce potential negative effect of exploiting the resourceson the environment.Twenty air-dried samples collected for this study were weighed and sealed for 28 days to enable them attain a state of secular equilibrium. They were subsequently analyzed for gamma-emitting radionuclides using Gamma-ray Spectrometer fitted with a calibrated Canberra vertical coaxial High purity Germanium Detector(HpGe) system. The radio nuclides identified with reliable regularity belong to the decay series of naturally occurring radio nuclides headed by 238U, 232Th and naturally occurring 40K. Result showed that the radiogenic composition of the clay overburden (0.631mSvy-1), shale-(0.193mSvyr-1), and bituminous sand (0.446mSvyr-1), are lower than the normal background value considered harmful to man.